Doubt and skepticism in antiquity and the renaissance - Zerba, Michelle (New York : Cambridge universty press, 2012)
This book is an interdisciplinary exploration of the forms and uses of doubt in the works of Homer, Sophocles, Aristophanes, Cicero, Machiavelli, Shakespeare, and Montaigne. Through a close analysis of the literary and philosophical texts by these key authors, Michelle Zerba argues that doubt is a defining experience in both antiquity and the Renaissance, consistently pushing the boundaries of thought and representation.
Includes bibliographical references and index.
Keywords: Belief and doubt - History; Skepticism - History